Pantoea ananatis: genomic insights into a versatile pathogen - Weller‐Stuart, Tania (Mol Plant Pathol, 2017)
SUMMARY: Pantoea ananatis, a bacterium that is well known for its phytopathogenic characteristics, has been isolated from a myriad of ecological niches and hosts. Infection of agronomic crops, such as maize and rice, can result in substantial economic losses. In the last few years, much of the research performed on P. ananatis has been based on the sequencing and analysis of the genomes of strains isolated from different environments and with different lifestyles. In this review, we summarize the advances made in terms of pathogenicity determinants of phytopathogenic strains of P. ananatis and how this bacterium is able to adapt and survive in such a wide variety of habitats. The diversity and adaptability of P. ananatis can largely be attributed to the plasticity of its genome and the integration of mobile genetic elements on both the chromosome and plasmid. Furthermore, we discuss the recent interest in this species in various biotechnological applications. TAXONOMY: Domain Bacteria; Class Gammaproteobacteria; Family Enterobacteriaceae; genus Pantoea; species ananatis. DISEASE SYMPTOMS: Pantoea ananatis causes disease on a wide range of plants, and symptoms can range from dieback and stunted growth in Eucalyptus seedlings to chlorosis and bulb rotting in onions. DISEASE CONTROL: Currently, the only methods of control of P. ananatis on most plant hosts are the use of resistant clones and cultivars or the eradication of infected plant material. The use of lytic bacteriophages on certain host plants, such as rice, has also achieved a measure of success.